2018
DOI: 10.1002/brb3.980
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on prefrontal activation during a verbal fluency task in children: A twin study using near‐infrared spectroscopy

Abstract: ObjectiveThe genetic and environmental influences on prefrontal function in childhood are underinvestigated due to the difficulty of measuring prefrontal function in young subjects, for which near‐infrared spectroscopy (NIRS) is a suitable functional neuroimaging technique that facilitates the easy and noninvasive measurement of blood oxygenation in the superficial cerebral cortices.MethodUsing a two‐channel NIRS arrangement, we measured changes in bilateral prefrontal blood oxygenation during a category versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…fNIRS has better temporal resolution than fMRI, better spatial resolution than EEG, can be used in naturalistic environments, is less susceptible to artifacts from movement, and can directly measure changes in blood oxygenation levels related to neural activation; however, it is limited to brain activity changes on and near the surface of the brain (Tak & Ye, 2014;Westgarth et al, 2021). fNIRS has only just begun to be included in family studies (e.g., Ohi et al, 2017;Sakakibara et al, 2018); it will be some time before the field has multiple estimates of familial resemblance for fNIRS indicators of cognitive regulation of emotion.…”
Section: Research Based On Neural Activity and Physiologymentioning
confidence: 99%
“…fNIRS has better temporal resolution than fMRI, better spatial resolution than EEG, can be used in naturalistic environments, is less susceptible to artifacts from movement, and can directly measure changes in blood oxygenation levels related to neural activation; however, it is limited to brain activity changes on and near the surface of the brain (Tak & Ye, 2014;Westgarth et al, 2021). fNIRS has only just begun to be included in family studies (e.g., Ohi et al, 2017;Sakakibara et al, 2018); it will be some time before the field has multiple estimates of familial resemblance for fNIRS indicators of cognitive regulation of emotion.…”
Section: Research Based On Neural Activity and Physiologymentioning
confidence: 99%
“…Despite its frequent use in both clinical and experimental settings, genetically-informed studies of verbal fluency have focused exclusively on total word production, rather than more specific switching indices. Multiple adult studies have shown both genetic and environmental contributions to performance on verbal fluency tasks (Hayiou-Thomas et al, 2006;Kavé et al, 2013;Kovas et al, 2005;Owens et al, 2011;Swan & Carmelli, 2002) and find that by middle age, approximately 45% of the variance verbal fluency performance is explained by genetic contributions (Gustavson et al, 2018;Jones-Odeh et al, 2016;Sakakibara et al, 2018). Only one study has focused on a developmental sample (Kavé et al, 2013), and that work was limited to 4-year-olds, who show only nascent executive abilities.…”
Section: Investigating Causal Links Between Environmental Structure and Developing Self-directed Ef In A Genetically Informative Samplementioning
confidence: 99%